Numerical investigation of the skip characteristics of a disk based on the coupled FEM-SPH method - Yan, Guo-Xin; Pan, Guang; Shi, Yao; Ma, Jian-Ting (Modern physics letters. B, Condensed matter physics, statistical physics, applied physics, 2019)
The skip phenomenon that may occur when a disk impacts water is a subject of perennial fascination for children as well as adults alike; it is also a fairly complex and highly nonlinear fluid-structure interaction problem. In this paper, the coupled FEM-SPH algorithm is used to numerically study the skip characteristics of disk impacting water. The critical conditions of the skip and the relationship between the initial velocity and the maximum skipping times are obtained. Moreover, the dissipation role of energy during the skipping process is discussed. Our conclusions can provide references for other similar issues, such as aircraft ditching, trans-medium vehicles, bouncing projectiles and so on.